The Messianic Davidic Expectations of Psalms 151A and 151B, and Their Theology - Maicol A. Cortés (TheoRhēma, 2023)
Psalms 151A and 151B (11QPs a 28:3–14), discovered at Qumran, narrate the story of the young David, particularly the accounts of 1 Sam 16–17. Scholars have studied Ps 151 using textual criticism, comparing its diﬀerent versions, or even looking at several translations. However, this study focuses on the theology and messianic expectations typical of the Second Temple literature. The study will concentrate on the translation and poetic analysis of the scroll to understand the emphasis the author wanted to communicate to his readers.